RELIGIOUS CONSCIOUSNESS OF SOCIETY AND ITS REFLECTION IN CONTEMPORARY ARTS OF TATARSTAN - R. Mukhametzyanova, Liliya; H. Kadyjrova, Lyajsan; В. Halmurzaeva Gaukhar (Gênero & Direito, 2020)
Various relations between the forms of social consciousness such as art and religion are formed in the process of the historical development of the spiritual culture of mankind. In this historical phenomenon, certain religions “choose” this or that system of arts, which in the most optimal way is capable of reproducing the spiritual atmosphere and religious practice of this religion. Fine arts as the emotional-figurative affirmation of religious ideas occupies a certain place in the system of religious values. In a bright and clear form, this process is manifested in the functioning of the developed world religions, whose structure is the most stable and defined, although historically it has, of course, evolved. The present article discusses the mythological and religious themes in the works by artists of Tatarstan of the years 1990s-2000s, which reflect, above all, the two main religions represented in Tatarstan – Islam and Christianity, and often regardless of the ethnic affiliation of certain artists. And the religious tolerance inherent in the Republic of Tatarstan, the dialogue of two cultures, are reflected in this interaction, the mutual influence of various religious denominations on the worldview, on the spiritual world of people, on the creativity of artists.